Culture of evaluation for learning according to students and teachers of a Mexican public university - Contreras Roldán, Sofía (2023)
Introduction: The culture of assessment for learning is one where the evaluation strategies employed seek to promote and improve student learning. Objective: to know the extent to which the culture of evaluation in a Mexican public university is oriented towards evaluation strategies for learning. Method: Two surveys were applied to 1,849 students and 545 teachers during 2022-1, considering random non-probability samples. Results: the teachers reported that the evaluation strategy that they dominate the most is the development of objective examinations, and to a lesser extent self-evaluation and co-evaluation; for its part, about half of students assessed that the use of these is of poor quality to regular, however, they claim to be satisfied with the use of formative assessment strategies by their teachers. Discussion: Convergences and divergences (teachers/students) were observed regarding the use, quality, and mastery of these evaluation strategies.